2017
DOI: 10.1177/2325967117712228
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Capitellum During Elbow Arthroscopy: A Comparison of 3 Portal Techniques

Abstract: Background:Capitellar osteochondritis dissecans (OCD) is a debilitating condition of unknown etiology for which various arthroscopic treatments are available. Prior data suggest that greater than 75% of the capitellum can be visualized arthroscopically through a dual lateral portal approach. However, there is no literature assessing arthroscopic visualization of the capitellum via alternative portals.Purpose:To determine the percentage of capitellum visualized using the dual lateral, distal ulnar and soft spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our results could show that arthroscopy of the elbow in the treatment of osteochondrosis dissecans has limitations in the accessibility of the entire articular surface. Even though Trofa and his colleagues could show a relatively good visualization of the capitellum with approximately 66.5% outlined during a standard arthroscopy, so far, no studies have presented the accessibility of the capitellar surface for example in nano-drilling, when more flexible instruments like K-wires are used [ 24 ]. This way our study contributed to the current literature as it displays the accessibility during arthroscopy and not only visualization and it presents a preoperative evaluation method as explained in detail in the materials and method section using sagittal MRI or CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results could show that arthroscopy of the elbow in the treatment of osteochondrosis dissecans has limitations in the accessibility of the entire articular surface. Even though Trofa and his colleagues could show a relatively good visualization of the capitellum with approximately 66.5% outlined during a standard arthroscopy, so far, no studies have presented the accessibility of the capitellar surface for example in nano-drilling, when more flexible instruments like K-wires are used [ 24 ]. This way our study contributed to the current literature as it displays the accessibility during arthroscopy and not only visualization and it presents a preoperative evaluation method as explained in detail in the materials and method section using sagittal MRI or CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Even though anatomical studies have shown the feasibility of the elbow joint for arthroscopic techniques in the past, due to a small working space and adjacent neurovascular structures, visualization of the joint remains an ongoing issue and gives room for improvement [ 22 , 23 ]. In a foregone study by Trofa et al it was shown, that 66.5% of the capitellum can be visualised during a standard elbow arthroscopy, the accessibility regarding the treatment options like micro-fracturing was not evaluated [ 24 ]. In our clinical experience and also studies have shown, the incomplete visualization and especially the accessibility of the capitellum continue to be a major challenge leading to poor patient outcomes, even though flexion and extension can provide a remedy [ 25 ].…”
Section: Introductionmentioning
confidence: 99%